2020
DOI: 10.1002/app.50000
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose triacetate/LUDOX‐SiO2 nanocomposite for synthesis of pervaporation desalination membranes

Abstract: A series of cellulose triacetate/Ludox-silica nancomposite pervaporation membranes was successfully prepared via solution casting, aiming to improve the performance of cellulose triacetate membranes for desalination. The fabricated nanocomposite membranes were characterized to study the membrane morphology, chemical composition, mechanical properties, and surface hydrophilicity. Furthermore, the desalination performance was investigated as a function of silica (SiO 2) loading (ranging from 1 to 4 wt%) and feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 59 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Meanwhile, membrane separation with its low energy consumption, ease of operation, and continuous separation is considered the most favorable chiral separation technique. [32][33][34][35] CTA membranes are extensively utilized in diverse applications, including desalination, [36][37][38][39] wastewater treatment, [40][41][42] and gas separation, 43,44 owing to their straightforward fabrication, high durability and stability. The six-membered ring of the CTA backbone contains chiral carbons, thus potentially enabling CTA to facilitate chiral recognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, membrane separation with its low energy consumption, ease of operation, and continuous separation is considered the most favorable chiral separation technique. [32][33][34][35] CTA membranes are extensively utilized in diverse applications, including desalination, [36][37][38][39] wastewater treatment, [40][41][42] and gas separation, 43,44 owing to their straightforward fabrication, high durability and stability. The six-membered ring of the CTA backbone contains chiral carbons, thus potentially enabling CTA to facilitate chiral recognition.…”
Section: Introductionmentioning
confidence: 99%
“…CTA membranes are extensively utilized in diverse applications, including desalination, 36–39 wastewater treatment, 40–42 and gas separation, 43,44 owing to their straightforward fabrication, high durability and stability. The six‐membered ring of the CTA backbone contains chiral carbons, thus potentially enabling CTA to facilitate chiral recognition 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the research conducted on the use of this technique in water desalination is scarce, as shown by a restricted number of papers [5,[11][12][13][14][15]. The membranes used in prior research on PV brine and seawater desalination included a PVA-based functional layer [16][17][18], a GO-based functional layer [19][20][21], an organic silica/silicate-based functional layer [22], cellulose membranes [23][24][25][26], and others [27][28][29]. The temperature of the feed was a critical parameter as it resulted in an increase in diffusivity and a decrease in viscosity when heated.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36] Cellulose and its derivatives have also been used in combination with silica particles for aerogels, desalination membranes, membranes for oil water separation, films for passive radiative cooling, filters for cigarette smoke, thermal insulation etc. [37][38][39][40][41][42][43] A straightforward process to facilitate infiltration and achieve homogenous distribution of silica into cellulose can enhance the processibility and scalability for fabrication of these functional materials.…”
Section: Introductionmentioning
confidence: 99%